Consciousness of Political Correctness in Gender Matters: A Transitivity Analysis of Reading Texts in Two English Textbooks Published in Great Britain and Malaysia in 1970s - Damayanti, Ika Lestari (EDUCARE, 2010)
ABSTRACT: There has been awareness of gender asymmetry in some texts including those in ELT materials. This paper, in compliance to augmenting awareness of gender asymmetry, attempts to discuss gender representations in ELT textbooks. I will look at the representations of females and males by using transitivity analysis of functional linguistics within both the clause and the sentence. Two ELT textbooks published in Great Britain and Malaysia in 1970s were chosen in order to see how females and males were portrayed in the early era of language awareness. From the findings, it is revealed that both ELT textbooks from different cultures were not conscious enough of âpolitical correctnessâ in gender matters. The number of female-male participants was unequal. Some males were described as being more active and competent whilst females being more passive and less competent than males. In some cases, femalesâ jobs were also represented as being less desirable. However, texts within Western culture represent females better than those within Eastern culture in terms of visibility and variety of job collocated to females. Hopefully, the present finding, from data in the 1970s, can be used as a gauge to measure progression of the use of language within educational material.Â Â KEY WORDS: ELT textbooks, transitivity, gender asymmetry, and the Great Britain and Malaysia in 1970s.About the Author: Ika Lestari Damayanti, M.A. is a Lecturer at the Department of English Education, Faculty of Art and Language Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. She can be reached at: ikadlovely@hotmail.com or ikadlovely@yahoo.com.sgÂ How to cite this article? Damayanti, Ika Lestari. (2010). âConsciousness of Political Correctness in Gender Matters: A Transitivity Analysis of Reading Texts in Two English Textbooks Published in Great Britain and Malaysia in 1970sâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.211-222. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 5, 2009); Revised (January 5, 2010); and Published (February 17, 2010).